Effect of Zeolite Modification via Cationic Exchange Method on Mechanical, Thermal, and Morphological Properties of Ethylene Vinyl Acetate/Zeolite Composites. (17th December 2013) - Zaharri, N. D.; Othman, N.; Ishak, Z. A. Mohd
Abstract : In this research, organozeolite filled ethylene vinyl acetate (EVA) composites were prepared in a melt-mixing process and followed by compression molding using hot press machine according to standard test specimen. Prior to mixing process, zeolite was modified via cationic exchange of alkylammonium ions. The effect of zeolite or organozeolite loading from 5 up to 25 volume percentages on the properties of EVA/zeolite composites was evaluated. A combination of Fourier Transform Infrared Radiation (FTIR) and scanning electron microscopy (SEM) coupled with energy dispersive X-ray (EDX) analysis were done to characterize the resultant organoclay. Tensile test was performed in order to study the mechanical properties of the composites. EVA filled with organozeolite showed better tensile properties compared to EVA filled with unmodified zeolite, which might be an indication of enhanced dispersion of organophilic clay in the composites. Meanwhile, morphological study using SEM revealed the fibrillation effect of organozeolite. Besides, thermal properties of the composites were also characterized by using thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results showed that the application of the cation exchange treatment increases both decomposition and melting temperature of EVA/zeolite composites.